2000
DOI: 10.1046/j.1439-0442.2000.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Insemination and Retrograde Sperm Transport in Dairy Cows

Abstract: To examine the efficiency of retrograde sperm transport following intraperitoneal insemination, live and dead spermatozoa were used at different concentrations, and sperm recovery from cervical mucus (0.5 ml) 2, 6, 12 and 24 h following insemination was evaluated. Forty lactating Friesian cows, in their second to fourth lactation period, were used in this experiment. Thirty-six cows received intraperitoneally either live or dead spermatozoa. Each group of six cows received one of three total sperm numbers of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The results of Lopez-Gatius and Yaniz (31) showed that following intraperitoneal insemination, there was passive sperm transport from the peritoneal cavity to the genital tract close to the time of ovulation, and suggested higher sperm retention in the genital tract when live as opposed to dead spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Lopez-Gatius and Yaniz (31) showed that following intraperitoneal insemination, there was passive sperm transport from the peritoneal cavity to the genital tract close to the time of ovulation, and suggested higher sperm retention in the genital tract when live as opposed to dead spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be transuterine migration of the embryo, although the physiological mechanism for this is unknown. Transperitoneal migration of the oocyte cannot be precluded (First 1954), as live or dead spermatozoa may also reach the tubular genital organs from the peritoneal cavity (López‐Gatius and Yániz 2000). The fact that all pregnancies were lost is consistent with earlier findings (unpublished) in which 14 contralateral gestations out of a total of 10 605 pregnancies diagnosed within a reproductive control programme were lost before 90 days of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Even when tightly embraced by the fimbriated extremities during estrus, a film of peritoneal fluid could be in contact with the gonad due to surface tension. This assertion receives strong support from the experimental approach of intra‐peritoneal insemination in domestic animals in which the highest levels of fertility were recorded with insemination shortly before the time of ovulation (15, 33). The sperm suspension would have gained the Fallopian tube(s) in a film of fluid propelled by the activity of dense tracts of cilia.…”
Section: Ovary To Ovarymentioning
confidence: 95%